Rare Dihydropyrimidine Dehydrogenase Variants and Toxicity by Floropyrimidines: A Case Report - Palmirotta, Raffaele; Lovero, Domenica; Delacour, Hervé; Le Roy, Audrey; Cremades, Serge; Silvestris, Franco (Frontiers in Oncology, 2019)
ABSTRACT Variations in the activity, up to absolute deficiency, of the enzyme dihydropyrimidine dehydrogenase (DPD), result in the occurrence of adverse reactions to chemotherapy, and have been included among the pharmacogenetic factors underlying inter-individual variability in response to fluoropyrimidines. The study of single-nucleotide polymorphisms of the DPYD gene, which encodes the DPD enzyme, is one of the main parameters capable of predicting reduced enzymatic activity and the consequent influence on fluoropyrimidine treatment, in terms of reduction of both adverse reactions and therapeutic efficacy in disease control. In this paper, we describe a patient with metastatic breast cancer showing signs of increased toxicity following capecitabine therapy. Analysis of the most frequent polymorphisms of the DPYD gene suggested a wild-type genotype but indicated a novel variant c.1903A>G (p.Asn635Asp), not previously described, proximal to the splice donor site of exon 14. After excluding the potential pathogenic feature of the newly-identified variant, we performed cDNA sequencing of the entire DPYD coding sequence. This analysis identified the variants c.85T>C and c.496A>G, which were previously described as pivotal components of the haplotype associated with decreased enzyme activity. The clinical case findings described in this study emphasise the importance of performing complete genetic analysis of the DPYD gene in order to identify rare and low frequency variants potentially responsible for toxic reactions to fluoropyrimidine treatment.